The Expert center for Taxonomic Identification - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The ETI is a non-profit organization set up in 1990 with the aim of concentrating and distributing diversity of information by means of multimedia computer technology. ETI has developed a user-friendly universal biodiversity software programme,...